Pengaruh Permainan Tradisional Ular Naga Terhadap Kemampuan Sosial Emosional Anak Usia Dini Kelas B Di Tk Negeri Pembina Kecamatan Ketahun Kebupaten Bengkulu Utara - Geiska Mendita Wardani; Evi Selva Nirwana (Peneliti.net, 2023)
The purpose of this study was to determine the effect of the dragon game on the social emotional development of class B early childhood in Pembina Kindergarten, Ketahun District, North Bengkulu Regency, and then to determine the direction of the influence of the dragon game on the social emotional development of class B early childhood in the Pembina Kindergarten, District Year of North Bengkulu Regency. This research is a field research (field research) with quantitative experimental methods with the research design used is between subject design with the pretest-posttest control group design model with research analysis using non-parametric statistics. The results of the study explained 1) there was an effect of the dragon game on the emotional development of early childhood class B in Pembina Kindergarten, Ketahun District, North Bengkulu Regency and 2) the direction of the influence of the dragon game on the social emotional development of class B early childhood in the Pembina Kindergarten, Ketahun District, Regency North Bengkulu is positive or better. We can see from the independent rank of the observation sample post-test experiment and post-test control observation 2. The social value of the experimental class children has increased compared to the class children where the experimental class gets an average of 23.00 and the experimental class gets an average the average is 8.00, while the indicators for each variable of the child's social ability experience an increase from the first post-observation to the second post-test with an average proportion of increase; 1) indicators of self-awareness of 90%, 2) indicators of a sense of responsibility for oneself and others of 83.33% and 3) social behavior of 69.66%. As well as using nonparametric data and validity test.